2015
DOI: 10.1039/c5dt00046g
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional lanthanide and silver ion co-doped nano-chlorapatites with combined spectroscopic and antimicrobial properties

Abstract: Nanocrystalline chlorapatites (Ca10(PO4)6Cl2) doped with lanthanide ions (Eu(3+), Er(3+) and Yb(3+)) and co-doped with silver ions (Ag(+)) were synthesized by a hydrothermal synthesis route. XRD, TEM, and SAED measurements indicated that the powders are single phased and crystallize with a hexagonal structure with good dispersion. The results showed well crystallized chlorapatite grains with a diameter of about 45 nm. The antimicrobial activity of the nanoparticles against Escherichia coli ATCC 11229 and ATCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…As investigated by Iconaru et al [ 75 ], there was no antimicrobial activity of Eu 3+ -doped hydroxyapatites detected against E. coli 25922. Our previous study also showed no effect of Eu 3+ -doped hydroxyapatites and chlorapatites against Gram-negative bacteria [ 76 , 77 ]. However, these materials differed in the concentration of Eu 3+ ions or contained other co-dopants, such as Sr 2+ ions.…”
Section: Resultsmentioning
confidence: 99%
“…As investigated by Iconaru et al [ 75 ], there was no antimicrobial activity of Eu 3+ -doped hydroxyapatites detected against E. coli 25922. Our previous study also showed no effect of Eu 3+ -doped hydroxyapatites and chlorapatites against Gram-negative bacteria [ 76 , 77 ]. However, these materials differed in the concentration of Eu 3+ ions or contained other co-dopants, such as Sr 2+ ions.…”
Section: Resultsmentioning
confidence: 99%
“…Although the last ionic additives incorporable into CAP will soon be off the list in terms of being integrated into CAP and limitedly characterized for their properties, it will be a while before even the tip of the iceberg of possibilities achievable through the synergy amongst different ionic dopants is revealed. Some of such simultaneous incorporations of two or more types of ions into CAP, such as silver and lanthanides [ 75 ], zinc and magnesium [ 76 ], selenite and manganese [ 77 ], europium and gadolinium [ 78 ], have already been tested for their multifunctional properties.…”
Section: Cap As a Foreign Ion Accommodatormentioning
confidence: 99%
“…Inorganic antibacterial agents possess advantages such as stability and safety. The antibacterial agents include ions such as copper, silver, and zinc [ 7 , 8 , 9 ], and several studies have shown that they can play important roles in the prevention or minimization of initial bacterial adhesion [ 10 , 11 ]. Metal ions can react with microbial membrane, causing structural changes and permeability.…”
Section: Introductionmentioning
confidence: 99%